Ultraviolet and biological effective dose observations at Gale Crater, Mars - Daniel Viúdez-Moreiras; María-Paz Zorzano; Mark T. Lemmon; Alberto G. Fairén; Alfonso Saiz-Lopez; Michael D. Smith (Proceedings of the National Academy of Sciences, 2025)
The incident ultraviolet (UV) irradiance on the surface of Mars is strongly sterilizing and plays a critical role in atmospheric and near-surface photochemistry. The Rover Environmental Monitoring Station (REMS) instrument, which includes the first UV sensor sent to Mars on board the Curiosity rover, has been measuring the UV irradiance at Gale Crater since 2012, providing ground-truth data regarding seasonal and short-term variability of the UV radiation at the surface of another planet. Here, we analyze the REMS UV measurements for a period of >5 Martian years to retrieve biological effective doses and other UV radiation quantities on the planetary surface that are key for different physicochemical processes. Our results reveal a previously unidentified complex UV radiation environment on the Martian surface, with dramatic short-term fluctuations capable of changing UV radiation doses by >30% in a few sols. We assess the viability of terrestrial microorganisms exposed to this UV radiation field and dispersed through the Martian atmosphere from a robotic spacecraft or human habitat. Our findings show that reducing microbial viability by 99% would require several hours of exposure to the Martian environment including during the daytime, a finding that may call for a reinforcement of planetary protection policies.